(untitled) (Research, Society and Development, 2022)
This study is a systematic review that aimed to identify which instruments are used to evaluate the quality of life (QoL) of patients with Alzheimer’s Disease (AD). AD is a chronic, progressive and neurodegenerative disease common in elderly people and your prevalence is increasing due to increased life expectancy. The pathological processes resulting from the progression of the pathology can generate profound disabilities and fragility, affecting affective, psychological and functional dimensions that intensify the impairment of QoL, as they compromise the psychosocial adaptation and interaction of the elderly with the environment. The evaluation of the QoL of cognitively compromised elderly people presents a series of challenges, not least because questions about the ability of these people with cognitive decline to make subjective judgments and about the point at which they become incapable of making them can also be raised, since that variations in memory, attention, judgment and communication deficits influence the ability of these individuals to understand issues or communicate their subjective states. This sistematic review conclued that currently the instrument more reliable and more used to evaluate the quality of life of patients with Alzheimer’s disease is the QoL-AD.